Cavitation of tumoral basement membrane as onset of cancer invasion and metastasis: physics of oncogenic homeorhesis via nonlinear mechano-metabolomics. (7th March 2016) - Prakash, Sai S
Abstract: In opening this duology, we present a physicochemical model of the evolution of malignant tumors (carcinomas) into metastases. The continuum-theoretic model, congruent with recent experimental evidence, analyzes the plausibility of neoplasia-induced cavitation or tensile yielding of the tumoral basement membrane (BM) to activate cancer invasion and metastasis. Normal BMs are semicrystalline sheets, ca 0.1–30 μ m-thick, and ca 500–1000× stiffer than the epithelial cells they ensheath. A specialized form of extra-cellular matrix (ECM), BMs are, however, distinctly constituted of tri-continuous networks of collagen-IV, laminin, and aqueous interstitial fluid with connector proteins; e.g. nidogens and perlecans. At the outset, we posit by physical analogy and inductive reasoning that a malignant tumor grows in size until reaching a threshold determined by its mechanochemical state vis-à-vis its microenvironment. This threshold is equated to the cavitation of a pathologically-softened (e.g. proteolyzed) BM that encapsulates the growing neoplasm. We test this postulate by constructing a tumor spheroid prototype consisting of normal and cancer cells that grows radially via the influx of water and nutrients while being constrained by the BM and the adhesome, chiefly cadherins and integrins. Next, we formulate a coupled continuum model based on the mechanics of fluid-solid interactions, exergy-dependent mechano-damped Monod kinetics for cell proliferation and apoptosis and the cellular bioenergetics of glucose–lactate symbiotic metabolism incorporating empirical data alone as parameters. Exergy is the available energy as adenosine triphosphate (ATP) molecules. This nonlinear 'mechano-metabolomics' model, where the tumor and the BM represent a mutually-interacting composite, is computationally solved via Comsol ® equation-based modeling routines to simulate realistic tumor growth dynamics and the elasto-plastic deformation of the BM. Our computations indicate the plausibility of BM cavitation and suggest epithelial-to-mesenchymal transitions (EMT) and/or invadopoiesis as corollaries, ostensibly due to stress-localized ruptures of the adhesome and the mechano-chemotactic flow of detached tumor cell(s) through the widening 'nanovoid'.